La minaccia ecologica come forma di comunicazione. Il punto di vista della teoria dei sistemi sociali di Niklas Luhmann - Alberto Cevolini (Università degli Studi di Torino, 2021)
In recent years, ecology has once again risen to the top of the political agenda, attracting the attention of the mass media system. This paper outlines how the social systems theory developed by Niklas Luhmann deals with ecological issues and what is the originality of this approach. It focuses on the ecological threat as a form of communication, on the operational closure of social systems in its relationship with causality, and on resonance. It finally shows that the pandemic COVID-19 could be investigated from this sociological viewpoint as a threat coming from the human environment.